Temperature assessment of Si1-xGex source/drain heterojunction NT-JLFET for gate induced drain leakage ‒ A compact model. (August 2021) - Thakur, Anchal; Dhiman, Rohit
Abstract: In this paper, we have investigated the impact of temperature ( T ) and drain bias voltage ( V ds ) on gate induced drain leakage (GIDL) in SiGe Source/Drain heterojunction silicon-nanotube junctionless field effect transistor (S/D Si-NT JLFET). We developed a temperature dependent model for surface potential, electric field E Z, L-BTBT induced I GIDL and full drain current I ds using 2-D Poison equation with suitable boundary conditions. We have also examined impact of temperature (activation energy) and drain bias voltage (electric field) on L-BTBT induced I GIDL . It is found that the increase in drain bias voltage causes 31.1% rise in I GIDL and elevation in temperature has 29.4% increase in I GIDL . Furthermore, we have examined impact of temperature on transconductance ( g m ) and output conductance ( g d ). The results demonstrated that temperature and drain bias voltage has significant impact on SiGe S/D NTJLFET, however, it is considerably less than the NTJLFET. Highlights: A compact model of drain current and impact of temperature along with drain bias has been studied in SiGe source/drain heterojunction NTJLFET. It is found that the increase in drain bias voltage cause 31.1% rise in I GIDL, however, elevation in temperature increase I GIDL by 29.4%. The elevation in temperature results in reduced tunnelling width at channel-drain interface and it leads to earlier triggering of L-BTBT induced GIDL. The higher drain voltage combined with higher temperature has more influence on the L-BTBT induced GIDL.